PENDAMPINGAN IMPLEMENTASI TINDAK LANJUT PP NO. 23 TAHUN 2018 BAGI PELAKU USAHA BERBENTUK KOPERASI, PERSEKUTUAN KOMANDITER, DAN FIRMA BAGI UMKM DI KECAMATAN CIPAYUNG JAKARTA TIMUR - Ekawati Jati Wibawaningsih; Lidya Primta Surbakti; Ratna Hindria Dyah Pita Sari; Munasiron Miftah; Ranti Nugraheni (LP2M STP Mataram, 2022)
The purpose of community service activities is to provide assistance for implementation PP No 23 tahun 2018 regarding tax reporting for MSME members. With this assistance, it is hoped that MSME members have knowledge and skill about calculating and reporting taxes for their businesses. With the knowledge and skills of MSMEs, they can calculate how much tax they have to pay, as well as how to report taxation in maintaining the going concern of their business. The training activities were carried out for MSMEs at the Cipayung sub-district office, East Jakarta. The participants of this assistance are members of MSMEs and also Jakpreneur members in East Jakarta District. This assistance is carried out by lecturers from the accounting study program at UPN Veteran Jakarta (UPNVJ) and is also assisted by students UPNVJ.